Targeting nucleus pulposus cell death in the treatment of intervertebral disc degeneration - Hong Sun; Jiajie Guo; Zhilin Xiong; Yong Zhuang; Xu Ning; Miao Liu (JOR Spine)
Abstract Background Intervertebral disc degeneration (IDD) is a progressive age‐related disorder characterized by the reduction in the number of nucleus pulposus cells (NPCs) and degradation of extracellular matrix (ECM), thereby leading to chronic pain and disability. The pathogenesis of IDD is multifaceted, and current therapeutic strategies remain limited. The nucleus pulposus (NP), primarily composed of NPCs, proteoglycans, and type II collagen, constitutes essential components for maintaining intervertebral disc (IVD) function and spinal motion. The disturbed homeostasis of NPCs is closely associated with IDD. Accumulating evidence increasingly suggests the crucial role of programmed cell death (PCD) in regulating the homeostasis of NPCs. Aims This review aimed to elucidate various forms of PCD and their respective roles in IDD, and investigate diverse strategies targeting the cell death of NPCs for IDD treatment. Materials & Methods We collected the relevant literature regarding PCD and their roles in the development of IDD. Subsequently, we comprehensively summarized the intricate association between PCD and IDD, and also explored the potential and application of cell therapy and traditional Chinese medicine (TCM) in the prevention and treatment of IDD. Results Current literature indicated that the PCD of NPCs was closely associated with the pathogenesis of IDD. Additionally, the development of targeted pharmaceuticals based on the mechanisms of PCD could effectively impede the loss of NPCs. Conclusion This review demonstrated that targeting the PCD of NPCs may be a promising strategy for the treatment of IDD.